MEMBANGUN KELUARGA BERKARAKTER: SINERGI ANTARA POLA ASUH, KOMUNIKASI, DAN KETELADANAN - Devi, Adaninggar; Trisiana, Anita; Putrialifia, Okysalma; Tri Nugroho, Faqih Desbi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study contributes to evaluating the significant relationship between parenting methods, communication techniques, and persistence in providing role models in shaping children's character within the family environment. One of the biggest challenges in parenting today is the discrepancy between what parents say and the actual actions witnessed by children. The method used in this study wa a mixed- method approach with a sequential explicative design. Quantitative data were collected through questionnaires completed by 42 respondents, while qualitative data came from in-depth interviews with three key informants. The results showed that the majority of respondents (61.9%) had created a comfortable atmosphere in communication. However, there was a significant gap in terms of role models, reaching 7.1%, which served as a major barrier. A strong collaboration between democratic parenting, open communication, and consistent role models proved to be an important foundation in shaping independent, honest, and disciplined characters in children to create a happy family.